The level of Internet usage and its role on democratization among selected states in the Arab region - Ang, Iana L.; De Paz, Mark Jacob Leonido; Del Rosario, Kristine Demilou (2013)
This study identifies twenty-two (22) selected states located in the Arab Region, namely; Algeria, Bahrain, Comoros, Djobouti, Egypt, Iran, Iraq, Jordan, Kuwait, Lebanon, Libya Arab Jamahiriy, Mauritania, Morocco, Oman, Qatar, Saudi Arabia, Somalia, Sudan, Syrian Ayab Republic, Tunisia, United Arab Emirates, and Yemen. These selected states in the Arab region have caught the attention of the international arena with their struggles for democratization. Those struggles in the region were mainly caused by problems that arose from dictatorial governments or absolute monarchies.